Optimizing Carica Waste Processing into Liquid Organic Fertilizer Using Bioconversion Techniques to Increase Agricultural Productivity in Kejajar District, Wonosobo - Bahlawan, Zuhriyan Ash Shiddieqy; Megawati, Megawati; Pradnya, Irene Nindita; Damayanti, Astrilia; Permanadewi, Indrasukma; Zakia, Maulida (Universitas Negeri Semarang, 2026)
This community service program aims to optimize the use of Carica (Carica pubescens) waste into liquid organic fertilizer through bioconversion techniques, while simultaneously increasing the capacity of MSMEs and farmer groups in Kejajar District, Wonosobo. Activities include outreach, training, and mentoring in the production of liquid organic fertilizer on a household scale using simple technology based on decomposer microbes. The results of the community service show an increase in partners' knowledge and skills in Carica waste fermentation techniques, as well as in the production of liquid organic fertilizer with physical, chemical, and microbiological properties suitable for organic farming. Analysis shows decrease in pH and color changes, a distinctive fermentation odor, and increases in nutrient content (N, P, K), along with variations in substrate concentration. In addition, participants received mentoring on digital marketing strategies to increase the product's economic value. This program contributes to reducing Carica industrial waste, providing alternative organic fertilizers, and empowering local communities to improve welfare based on regional potential.